2015
DOI: 10.1039/c4nj01411a
|View full text |Cite
|
Sign up to set email alerts
|

A simple and effective 1,2,3-triazole based “turn-on” fluorescence sensor for the detection of anions

Abstract: 1,2,3-Triazole based chemosensor is synthesized using “Click chemistry” approach. Addition of fluoride ion “turn-on” the fluorescence response of probe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 105 publications
7
42
0
Order By: Relevance
“…At a higher concentration of approximately one equivalent, it splits again into two distinct resonances. These results are in accordance with the previously reported PTP sensor from our group [49]. The initial downfield and later upfield shifts of the H2 phenyl proton showed the impact of fluoride binding on the ring.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…At a higher concentration of approximately one equivalent, it splits again into two distinct resonances. These results are in accordance with the previously reported PTP sensor from our group [49]. The initial downfield and later upfield shifts of the H2 phenyl proton showed the impact of fluoride binding on the ring.…”
Section: Resultssupporting
confidence: 83%
“…At higher concentrations (2-4 equivalents), the doublet for HF 2 − ion at −144 ppm was clearly observed ( Figure S11) [59,60]. In comparison to the previously reported sensor, PTP [49], from our group, the 1 H-NMR studies with NpTP showed similar observations. The phenolic -OH proton was significantly affected but the aryl core (phenyl in PTP and the naphthyl in NpTP) was not.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations